(untitled) (Jurnal Manajemen dan Kewirausahaan, 2012)
This study aims to investigate factors that determine the structure of capital in existing firms in the mining sector in ASEAN countries. This study also examines whether there are differences in capital structure determination on these companies. The sample size consists of 70 companies that exist in the mining sector with sample criteria used is the company publishes a complete financial report and is available in the database Osiris. The dependent variable in this study is debt, while the independent variables are profitability, firm size, asset tangibility, firm growth, and non-debt tax shield. This study applies a pooled least square approach. The results show that the factors determining the debt policy are the profitability, firm size, tangible assets and the growth rate, whereas non-debt tax shield has no significant effect. The study also finds that there is no real difference in practice between the use of debt in the six ASEAN countries.